A Comparative Study of Drug-Eluting Stents and Bare-Metal Stents in Coronary Artery Disease - Akhtar, Syed Ahsan; Khan, Farhat Ullah; Afzal, Zeeshan; Hafeez, Muhammad; Parvez, Muzdalfa (Indus Journal of Bioscience Research, 2025)
Introduction: Coronary artery disease (CAD) holds the position as a top health issue that causes sickness and death throughout the global community. PCI represents a fundamental treatment approach, but the selection between DES and BMS medication delivery systems determines patient results. Objective: The research studied the medical success rates and safety characteristics between drug-eluting and bare-metal stents when used in PCI procedures for coronary artery disease. Materials and Method: Between January 2021 and June 2021, prospective comparative research was done at Department of Cardiology, Hayatabad Medical Complex, Peshawar. Two hundred patients joined the research into which they received either DES or BMS treatment (DES included 100 patients, and BMS included 100 patients). The study measured baseline patient data in addition to procedural success rates together with six-month clinical results. Results: Patients with DES experienced better outcomes than BMS patients because their restenosis rate was 6% lower and target lesion revascularization rate was 11% lower. The study results showed no statistically significant differences in mortality and myocardial infarction rates between groups. Conclusion: The clinical outcomes of DES prove better than those of BMSs, and medical authorities regard them as the go-to stenting solution for most PCI procedures.